Genocide : New Perspectives on its Causes, Courses and Consequences - Üngör, Uğur Ümit, 1980- (Studies of the NIOD Institute for War, Holocaust and Genocide Studies, 2020)
The twentieth century has been called, not inaccurately, a century of genocide. And the beginning of the twenty-first century has seen little change, with genocidal violence in Darfur, Congo, Sri Lanka, and Syria. Why is genocide so widespread, and so difficult to stop, across societies that differ so much culturally, technologically, and politically? That is the question that this collection addresses, offering a range of perspectives from different disciplines to attempt to understand the pervasiveness of genocidal violence.